2014
DOI: 10.1007/s00706-014-1271-0
|View full text |Cite
|
Sign up to set email alerts
|

Base-catalyzed cyclization of Ugi-adducts to substituted indolyl based γ-lactams

Abstract: Post-condensation cyclization of Ugi adducts from the condensation of 2-formylindole, isocyanides, amines, and 3-chloropropanoic acid was performed selectively in the presence of K 2 CO 3 to form a series of novel substituted c-lactams.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…Shiri and coworkers demonstrated a base‐mediated post‐Ugi cyclization strategy to leading to biologically relevant γ‐lactams 37 (Scheme 12). [47] Ugi adduct 36 derived from 2‐formylindole, (aliphatic/aromatic) amines, 3‐chloropropanoic acid, and isocyanides underwent highly selective intramolecular cyclization to furnish a novel series of indolyl‐based γ‐butyrolactams 37 .…”
Section: Base‐mediated Post‐ugi Transformationsmentioning
confidence: 99%
“…Shiri and coworkers demonstrated a base‐mediated post‐Ugi cyclization strategy to leading to biologically relevant γ‐lactams 37 (Scheme 12). [47] Ugi adduct 36 derived from 2‐formylindole, (aliphatic/aromatic) amines, 3‐chloropropanoic acid, and isocyanides underwent highly selective intramolecular cyclization to furnish a novel series of indolyl‐based γ‐butyrolactams 37 .…”
Section: Base‐mediated Post‐ugi Transformationsmentioning
confidence: 99%
“…In a parallel investigation, the synthesis of indole-linked -lactams 80 [where Ar = 2-(1H-indole)] via a two-step Ugi-4CR followed by a K 2 CO 3 -mediated S N 2 cyclization in DMF at 100 °C was reported by Shiri and co-workers. 56 In 2012, Hulme and co-workers 57 developed a one-pot, two-step methodology for the synthesis of 1,5-disubstituted-tetrazole-linked -lactams 82 by reacting keto-ester…”
Section: Scheme 16 Syntheses Of -Lactams 69mentioning
confidence: 99%
“…Shiri et al ( 2014 ) have reported a selective synthesis for a series of novel indolyl based γ-lactams 3b by cyclization of Ugi-adducts 3a in the presence of K 2 CO 3 in DMF at 100°C within few hours (Scheme 2 ). Under the optimum conditions, adducts derived from activated anilines underwent the reaction smoothly and gave access to the corresponding lactams in moderate to good yields.…”
Section: Five-membered Heterocyclesmentioning
confidence: 99%